Outcomes of Degenerative Cervical Myelopathy From The Perspective of Persons Living With the Condition: Findings of a Semistructured Interview Process With Partnered Internet Survey. Issue 3 (April 2022) - Davies, Benjamin M.; Munro, Colin; Khan, Danyal Z.; Fitzpatrick, Siobhan M.; Hilton, Bryn; Mowforth, Oliver D.; McNair, Angus G. K.; Sadler, Iwan; Kotter, Mark R. N.
Study Design: Mixed-methods cross-sectional study. Objectives: Degenerative cervical myelopathy (DCM) is a common and disabling condition. While classically, assessment and diagnosis has focused on neuromuscular symptoms, many other disabilities have been linked. The aim of this study was to explore the consequences of DCM for those with lived experience, producing a long list to inform the development of a core outcome set for DCM research. Methods: A 2-stage process was used: a focus group session of people with DCM (PwCM) and their supporters (n = 8) discussed the impact of DCM. This was used to develop a preliminary list of consequences, which were then placed into a survey of an online community of DCM sufferers (n = 224). Survey participants were asked to tick the consequences that they had experienced and given the opportunity to submit additional. Additional consequences were reviewed by a group of healthcare professionals and PwCM and included if not already represented. Demographic information including disease severity, age, and sex were captured for sampling comparison. Results: A total of 52 outcomes were identified from the focus group and nominally divided into 2 categories; symptoms (36 outcomes) and handicaps (18 outcomes), and further evaluated using a survey. All outcomes were recognized by at least 5% of respondents. A further 16 outcomes were added following the survey. Conclusions: A list of DCM consequences has been defined from the perspective of PwCM. This will now be evaluated as part of AO Spine RECODE-DCM, an international multistakeholder collaboration to establish a core outcome set for research.